IJCM_185A: Prevalence and Predictors of hypertension among adult population of rural health training center of a medical college in central karnataka- A Cross Sectional study - Hebballi Pooja B; Aurupa MS; Nitin SG (Wolters Kluwer Medknow Publications, 2024)
Background: Cardiovascular Diseases [CVDs] are the most common cause of death globally. Among the risk factors for CVDs, hypertension (HTN) is associated with the strongest evidence of causation. In India, only 12% people with HTN have their Blood Pressure under control. The Knowledge about HTN and risk factors plays a major role in its prevention and management. With limited studies in rural India about the same, this study was conducted. Objectives: 1] To estimate the prevalence of hypertension in the study area 2] To determine the risk factors for hypertension among hypertensives of study area 3] To assess knowledge about hypertension among the hypertensives of study area. Methodology: A Survey on screening for Hypertension was conducted in rural health training center Avargolla village of Davangere district, Karnataka. A Community based cross sectional study was conducted among hypertensive adult population aged 30yrs and above through Universal sampling technique. Data was collected by in-person interview using questionnaire on risk factors, knowledge about the causation, consequence and prevention of the disease and by physical measurements of BMI and Waist to Hip ration. Data was analysed using of SPSS software. Results: Majority of the study participants were females 75%. More than 55% had no family history of hypertension. Out of 90% who were on treatment, less than 77% were on regular medications. Diabetes was the most common associated co-morbidity seen. 86% of the study population consumed less than 5 servings of fruits & vegetables per day and <600METS of physical activity. Majority of them reported as high salt intake and stress to be major causative factor. Conclusion: Healthy weight and good knowledge on HTN play a major role in the management of disease. Most of the participants had no family history of disease signifying the first generational onset of the disease.